ON INTEGRATION OPTIONS OF UKRAIN FOREIGN POLICY - K. P. Borishpolets; S. I. Chernyavskiy (Vestnik MGIMO-Universiteta)
The article evaluates the impact of domestic political regional imbalance and inter-elite divisions of Ukraine in its choice of guidelines for integration. The main sphere of Ukrainian economy is controlled by more than ten financial industrial groups that actively lobby their interests in the policy. The Ukrainian elite is far from establishing the optimal balance between “Western” and “Eastern” vectors of integration cooperation. We believe that the reduction of tension between «Western» and «Eastern» vectors of integration policy of Ukraine in the short term is unlikely. Apparently, the choice in favour of rapprochement with the EU has already been made. But the peculiarity of this choice is the lack of completeness, the more that the question of who and in what volume will be able to sponsor a «European path» of the Ukrainian elite remains open